INHERITANCE STUDIES THROUGH COMBINING ABILITY FOR MORPHOLOGICAL AND YIELD TRAITS IN F POPULATIONS OF BRASSICA NAPUS L. - S. Gul; R. Uddin; N. U. Khan; M. Arif; R. Goher; M. Zakaria (Journal of Animal and Plant Sciences, 2018)
Inheritance study was carried out through combining ability for identification of potential parental cultivars, F hybrids, 1 and nature of gene action involved in morphological and yield traits in 8 × 8 diallel crosses of Brassica napus L. Genotypes revealed highly significant differences for all the traits i.e., days to 50% flowering, primary branches per plant, pods per main raceme, pod length and seed yield per plant. Mean squares due to general ( GCA), specific (SCA) and reciprocal combining ability ( RCA) were highly significant for all the studied traits, which revealed imperative role 2 2 2 of dominance, additive, and maternal effects. Comparatively higher values of ÃSCA than ÃGCA and ÃRCA with less 2 2 than unity ratios of ÃGCA/ÃSCA showed the predominance of non-additive gene action for the inheritance of the studied traits followed by maternal effects. Parental cultivars, Abassin-95 and Punjab Sarsoon were identified as best general combiners and in combination with other genotypes performed better for majority of the traits. The F hybrids 1 i.e., Rustam Canola × Faisal Canola, Punjab Sarsoon × Dunkled and Dunkled × Rainbow showed prominent SCA and best mean performance for studied traits. Therefore, the involvement of high and low general combiners performed well in the synthesis of superior F populations of rapeseed. 1 Brassica napus L. import of edible oil, it is imperative to develop improved
Keywords: Diallel crosses; GCA and SCA; Additive and non-additive gene action; Morphological and yield traits